GALLERY WALK: AN ALTERNATIVE LEARNINGSTRATEGY FOR STUDENTS’WRITING ACHIEVEMENT - Rosdiana; Indah Sari (Getsempena English Education Journal, 2019)
This study aims to improve students' ability to write complimenting English texts. The subjects of this study were 28 students of class X-IPA1 SMA 5 Banda Aceh. This research is a classroom action research (CAR) consisting of 2 cycles. Each cycle includes planning (planning), implementation (Action), observation (Observation), and reflection (Reflection). The data of this study were collected through performance, student observation sheets and management of learning by the teacher. The results showed that the students' ability to write English complimenting texts in the first cycle reached 60.09% and in the second cycle increased to 83.33% of students who achieved KKM 75. This means that the established indicators have been reached which determined that this study was successful if 85% of students reached KKM 75. By thus it can be concluded that the application of the Gallery Walk method can improve capabilitiesstudents in writing a complimenting texts. In this connection, it is recommended that teachers apply the Gallery Walk method in teaching English, especially forteaching writing skills.